2016
DOI: 10.1016/j.polsoc.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Teaching policy analysis in China and the United States: Implications for curriculum design of public policy programs

Abstract: Rapid worldwide growth in public policy education now offers excellent opportunities to assess the development of the field from a comparative perspective. Our analysis, which examines recent trends in public policy education by comparing public policy analysis courses taught in professional degree programs in China and in the United States, reveals considerable disparities in these curricula as taught in the two countries. Surprisingly, these differences have emerged primarily through disciplinary foci, exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Policy courses were often the result of return migration, with scholars who had previously pursued their studies in the West starting to teach policy courses in their countries of origin (Yildiz et al 2011;Kuo and Kuo 2012). In other instances, new schools and programs were created to cater to the rising demand for professional policy analysts and policy advisors, who were supposed to deal with the increasing complexity of policy challenges facing governments (He et al 2016). In Brazil and East Asia, the provision of public affairs education came as a response to changes in the region's political, social, and economic systems, including the transition toward democracy (Gomes et al 2016;Wu et al 2012).…”
Section: Global Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…Policy courses were often the result of return migration, with scholars who had previously pursued their studies in the West starting to teach policy courses in their countries of origin (Yildiz et al 2011;Kuo and Kuo 2012). In other instances, new schools and programs were created to cater to the rising demand for professional policy analysts and policy advisors, who were supposed to deal with the increasing complexity of policy challenges facing governments (He et al 2016). In Brazil and East Asia, the provision of public affairs education came as a response to changes in the region's political, social, and economic systems, including the transition toward democracy (Gomes et al 2016;Wu et al 2012).…”
Section: Global Expansionmentioning
confidence: 99%
“…Scholars refer to this phenomenon as internationalization in the policy sciences (Fritzen 2008;Henderson and Terry 2014). Clearly, this expansion provides scholarly opportunities for comparatively assessing the development, content, and nature of policy education (He et al 2016), which, in turn, may produce insights and lessons for enhancing the quality of policy education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already noted, the most well-articulated guidelines on how public policies should be formulated are to be found in policy analysis. A recent review has revealed that policy analysis is still predominantly positivist (He et al, 2016), and the core textbooks include those by Weimer and Vining (2016), Bardach and Patashnik (2015), Dunn (2016) and Patton et al (2016) 1 . The traditional textbooks mentioned above have been revised many times, and some efforts have been made to make them fit more in accordance with current developments.…”
Section: Traditional Guidelines On Policy Formulationmentioning
confidence: 99%
“…The second point is that the narrative on PA higher education usually relies on evidence gathered from qualitative and quantitative analyses of academic curricula (and infrequently of faculty’s disciplinary backgrounds) (e.g., Connaughton and Randma, 2002; Hajnal, 2003; Kickert, 2008; Hajnal, 2015; Brans and Coenen, 2016; He et al, 2016; Pal and Clark, 2016; Staroňová and Gajduschek, 2016). Especially in comparisons across countries, typologies or morphologies of schools or programs in PA usually boil down to an assessment of disciplinary identity, typically defined in terms of what is taught.…”
Section: Explaining Diversity and Change In Pa Education In Ceementioning
confidence: 99%